Inclusive Language for Digital Inclusion: A Case Study of the Self-Determination Perspective in Lon Malang, Madura - Bima Kurniawan; Dede Rosyadi ZA; Tri Pujiati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Language gaps between tourism managers and visitors often become barriers to effective information delivery. This study aims to identify the language choices used in tourism promotion at the Lon Malang ecotourism destination. A qualitative approach with a case study design was employed through in-depth interviews with managers and visitors, observations of promotional activities, as well as documentation and literature review. The findings reveal that proficiency in the Indonesian language is a key factor enabling visitors to understand promotional messages and fully enjoy the tourism experience. Meanwhile, the use of English is considered to enhance digital information access and strengthen Lon Malang’s image as an inclusive destination open to international tourists. Furthermore, the study highlights that meeting digital information needs is an essential aspect of promotional strategies, particularly in reducing the digital divide among visitors. Overall, this research emphasizes that the implementation of inclusive language and the improvement of digital literacy are strategic steps toward developing an equitable, sustainable, and accessible tourism promotion system for all visitors.